Dexamethasone mimics aspects of physiological acclimatization to 8 hours of hypoxia but suppresses plasma erythropoietin. - Liu, C; Croft, Q; Kalidhar, S; Brooks, J; Herigstad, M; Smith, T; Dorrington, K; Robbins, P (2013)
Dexamethasone ameliorates the severity of acute mountain sickness (AMS) but it is unknown whether it obtunds normal physiological responses to hypoxia. We studied whether dexamethasone enhanced or inhibited the ventilatory, cardiovascular, and pulmonary vascular responses to sustained (8 h) hypoxia. Eight healthy volunteers were studied, each on four separate occasions, permitting four different protocols. These were: dexamethasone (20 mg orally) beginning 2 h before a control period of 8 h of air breathing; dexamethasone with 8 h of isocapnic hypoxia (end-tidal Po(2) = 50 Torr); placebo with 8 h of air breathing; and placebo with 8 h of isocapnic hypoxia. Before and after each protocol, the following were determined under both euoxic and hypoxic conditions: ventilation; pulmonary artery pressure (estimated using echocardiography to assess maximum tricuspid pressure difference); heart rate; and cardiac output. Plasma concentrations of erythropoietin (EPO) were also determined. Dexamethasone had no early (2-h) effect on any variable. Both dexamethasone and 8 h of hypoxia increased euoxic values of ventilation, pulmonary artery pressure, and heart rate, together with the ventilatory sensitivity to acute hypoxia. These effects were independent and additive. Eight hours of hypoxia, but not dexamethasone, increased the sensitivity of pulmonary artery pressure to acute hypoxia. Dexamethasone, but not 8 h of hypoxia, increased both cardiac output and systemic arterial pressure. Dexamethasone abolished the rise in EPO induced by 8 h of hypoxia. In summary, dexamethasone enhances ventilatory acclimatization to hypoxia. Thus, dexamethasone in AMS may improve oxygenation and thereby indirectly lower pulmonary artery pressure.